PELATIHAN INOVATIF OLAHAN SINGKONG GUNA MENDUKUNG PROGRAM MBKM MAHASISWA AKUNTANSI UNIVERSITAS INDO GLOBAL MANDIRI - Aini, Nur; Hertati, Lesi; Asharie, Asmawati (Transpublika Publisher, 2022)
Cassava is a typical Indonesian plant that can be processed into various foods Cassava or commonly known as cassava or cassava, is an annual tropical and subtropical tree from the Euphorbiaceae family. Cassava is usually used as processed food because of its high carbohydrate content, while the leaves are usually used as vegetables. The purpose of this research is to inform the public about how cassava is processed into cassava chips to help the community generate income from selling cassava chips of various flavors. The method or plan that is carried out is to carry out direct training to sweet potato sellers in the activity of processing sweet potatoes into cassava chips and this uses qualitative methods. which is documentation. With this implementation, the results of the activity are obtained, namely, it is hoped that from processing cassava, the community will know what we can process from cassava, to increase the potential that exists in society, I am an accounting student Indo Global Mandiri University students are trying to help develop this research innovation entitled